Acceptance and Use of Mobile-Assisted Language Learning by Higher Education Language Teachers - Gustavo García Botero; Diep Anh Nguyet; Jacqueline García Botero; Chang Zhu; Frederick Questier (Lenguaje, 2022)
Mobile-assisted language learning (MALL) is increasingly gaining attention from educational stakeholders. This quantitative study implements the Unified Theory of Acceptance and Use of Technology (UTAUT) model with the added variable of attitude. The participants were 89 Colombian higher education language teachers who shared their views on MALL via an online questionnaire. The results indicate that teachers’ behavioral intention is influenced by their attitude, social influence and facilitating conditions. The study also highlights the importance of including use behavior in the measurement model: teachers who scarcely use MALL express stronger intentions to use it when compared to teachers with high MALL use, resulting in a negative correlation between behavioral intention and use behavior.